ADMINISTRASI KEPEGAWAIAN SIPIL TINGKAT LOKAL DALAM PEREKRUTAN PEGAWAI NEGERI SIPIL (STUDI KASUS PENGELOLAAN SISTEM REKRUITMEN CPNS KABUPATEN BADUNG TAHUN 2012) - Semara Putra, I Gede Made Pastika; Erviantono, Tedi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2014)
ABSTRACT The problem about officialdom in Indonesia is endless. many problems that occur in it starts from the smallest to the covers broad aspects. In November 2012, in Indonesia, news emerged that becameÂ  one of the topic. That is about it was found indication of irregularities in the recruitment process of employees that occurredÂ  in Badung regency. Problems that arise when it is the difference in the results of tests conducted CPNS in Badung district in 2012 between results of the Regional Employment Board, Education and Training (BKD-DIKLAT) in Badung regency with results published online by the Ministry of Administrative Reform state reforms (Kemenpan-RB). From that problem, the fact is in 2012 when we talk about mechanism of recruitment and job description of the government about that thing was manage in rules of Kepala Badan Kepegawaian Negara number 9 in 2012. Keyword : Recruitment System , CPNS Test